Quantitative characterization and origin of differences in pore parameter distribution: A case study of the lower cambrian longwangmiao formation in the gaoshiti area of central Sichuan Basin - Qu, Haizhou; Yan, Zanxu; Zheng, Chao; Xu, Wei; He, Fuwei; Sun, Qimeng; Zhang, Xinyu; Li, Minxing (Frontiers in Earth Science, 2023)
The research on the developmental characteristics and evolution process of pores in dolomite reservoirs is a hot spot in petroleum geology. In this paper, taking the dolomite reservoirs of the Longwangmiao Formation in the Gaoshiti area as an example, the differential distribution and evolution of pore parameters have been systematically studied combined with downhole cores, logging, cast thin sections, and scanning electron microscope data. We used statistical methods and image analysis techniques to quantitatively characterize the pore distribution of the Longwangmiao Formation in the study area. Moreover, the factors controlling the distribution of pores in the dolomite of the Longwangmiao Formation were identified, namely, lithology, sedimentary facies and diagenesis. Finally, the evolution mode of pores of the Longwangmiao Formation was constructed. The results show that the main types of pores developed in the Longwangmiao Formation in the study area include intergranular and intragranular dissolved pores, intercrystalline dissolved pores and mold pores. Among them, the intergranular dissolved pores are the main pore type. The pores with surface porosity higher than 0.5% in the Long 2 Member in the study area account for 46% of the total pores, while those in the Long 1 Member account for 25.5%. Therefore, the degree of development of pores in the Long 2 Member is better than the Long 1 Member. In addition, the granular dolomite in the grain shoal facies is favorable for the formation of large-scale pores, and the oolitic dolomite is the most favorable reservoir type. The most favorable factors for the development of pores are the atmospheric freshwater dissolution and dolomitization in the quasi-contemporaneous period; the former caused the formation of a large number of intergranular dissolved pores, while the dolomitized particles and their ring-edge cements in the latter promoted the retention of residual intergranular dissolved pores. The dissolution, dolomite cementation and hydrothermal action in the burial stage promoted the reformation of pores.